Step
*
1
1
1
2
of Lemma
int-to-ring-mul
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. n : ℤ
5. 0 < n
6. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|)))
7. x : ℤ
8. |x| < n
9. y : ℤ
10. ¬|x| < n - 1
11. x = (-(n - 1)) ∈ ℤ
⊢ int-to-ring(r;(-(n - 1)) * y) = (int-to-ring(r;-(n - 1)) * int-to-ring(r;y)) ∈ |r|
BY
{ (CaseNat 1 `n'⋅ THEN Reduce 0) }
1
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. n : ℤ
5. 0 < n
6. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|)))
7. x : ℤ
8. |x| < n
9. y : ℤ
10. ¬|x| < n - 1
11. x = (-(n - 1)) ∈ ℤ
12. n = 1 ∈ ℤ
⊢ int-to-ring(r;(-0) * y) = (int-to-ring(r;-0) * int-to-ring(r;y)) ∈ |r|
2
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. n : ℤ
5. 0 < n
6. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x * y) = (int-to-ring(r;x) * int-to-ring(r;y)) ∈ |r|)))
7. x : ℤ
8. |x| < n
9. y : ℤ
10. ¬|x| < n - 1
11. x = (-(n - 1)) ∈ ℤ
12. ¬(n = 1 ∈ ℤ)
⊢ int-to-ring(r;(-(n - 1)) * y) = (int-to-ring(r;-(n - 1)) * int-to-ring(r;y)) ∈ |r|
Latex:
Latex:
1.  r  :  Rng
2.  a1  :  \mBbbZ{}
3.  a2  :  \mBbbZ{}
4.  n  :  \mBbbZ{}
5.  0  <  n
6.  \mforall{}x:\mBbbZ{}.  (|x|  <  n  -  1  {}\mRightarrow{}  (\mforall{}y:\mBbbZ{}.  (int-to-ring(r;x  *  y)  =  (int-to-ring(r;x)  *  int-to-ring(r;y)))))
7.  x  :  \mBbbZ{}
8.  |x|  <  n
9.  y  :  \mBbbZ{}
10.  \mneg{}|x|  <  n  -  1
11.  x  =  (-(n  -  1))
\mvdash{}  int-to-ring(r;(-(n  -  1))  *  y)  =  (int-to-ring(r;-(n  -  1))  *  int-to-ring(r;y))
By
Latex:
(CaseNat  1  `n'\mcdot{}  THEN  Reduce  0)
Home
Index